Data-driven business model innovation in SMEs - Ernola, Mona (My University, 2021)
The exponentially increasing speed of data generation and success stories of data-driven business opportunities have increased the interest among established organizations to leverage data for new business opportunities. Business model innovation is known as an activity or process in which companies innovate their value proposition, value creation and value capture logic by altering or developing new elements to their business models. This thesis aims to explore the infusion of data and business model innovation. While most data-driven business model innovation literature focuses on exploring the phenomenon in the context of large organizations or startups, this study aims to increase understanding of how established SMEs, a significant source of economic performance and job creation, leverage data and develop business models to support new data-driven innovations. The study was conducted as a descriptive qualitative multiple-case study with 12 SMEs participating in a business program and actively developing their business with the aid of data during a six-month long program. The main source of data was collected through semi-structured interviews with the participating SMEs at the end of the pro-gram. The interviewees consisted of the case firms’ top-management and innovation and development directors. The findings indicate that data-driven business model innovation is a complex pro-cess for established businesses with manifold effects to their existing business. Accord-ing to the findings, SMEs leverage data for both internal improvements as well as new business development. Leveraging data allows firms to move towards more scalable business models benefitting from more stable, recurring business such as longer customer relationships, better reach of customers through new channels and additional revenue streams. Conducting business model innovation adds to organizational complexity which firms address by running parallel business models or separating the emerging and existing businesses from each other. The study findings add empirical evidence to prior literature and assist involved practitioners in business model innovation activities by increasing understanding of data-driven opportunities and business model innovation processes in SMEs.

Eksponentiaalisesti kasvava datan tuotantonopeus ja datapohjaisten liiketoimintamahdollisuuksien menestystarinat ovat lisänneet vakiintuneiden organisaatioiden kiinnostusta hyödyntää dataa uusissa liiketoimintamahdollisuuksissa. Liiketoimintamalli-innovaatio tunnetaan toimintana tai prosessina, jossa yritykset innovoivat arvolupaustaan, arvonluontiaan ja ansaintalogiikkaansa muuttamalla tai kehittämällä uusia elementtejä liiketoimintamalleihinsa. Tämän työn tavoitteena on tutkia datan ja liiketoimintamalli-innovaatioiden yhteyttä. Suurin osa aiemmasta liiketoimintamalli-innovaatiokirjallisuudesta keskittyy ilmiön tutkimiseen suurten organisaatioiden tai start-up-yritysten kontekstissa, mutta tämän tutkimuksen tavoitteena on lisätä ymmärrystä siitä, kuinka vakiintuneet pk-yritykset, jotka ovat merkittävä lähde taloudelliselle suorituskyvylle ja työpaikkojen luomiselle, hyödyntävät dataa ja kehittävät liiketoimintamallejaan tukemaan uusia datalähtöisiä innovaatioita. Tutkimus toteutettiin kuvailevana laadullisena monitapaustutkimuksena 12 pk-yrityksen kesken, jotka kehittivät aktiivisesti liiketoimintaansa datan avulla kuuden kuu-kauden mittaisen yritysohjelman aikana. Pääasiallinen tietolähde työlle kerättiin puolistrukturoiduilla haastatteluilla. Haastateltavat koostuivat tapausyritysten ylimmästä johdosta sekä innovaatio- ja kehitysjohtajista. Tulokset osoittavat, että datalähtöinen liiketoimintamalli-innovaatio on vakiintuneille yrityksille monimutkainen prosessi, jolla on monia vaikutuksia olemassa olevaan liike-toimintaan. Tulosten mukaan pk-yritykset hyödyntävät dataa sekä sisäisiin kehitystarpeisiin että uuden liiketoiminnan kehittämiseen. Datan hyödyntäminen tarjoaa yrityksille mahdollisuuden siirtyä kohti skaalautuvampia liiketoimintamalleja, joissa yritykset hyötyvät pitkäkestoisista asiakassuhteista, uusien kanavien mahdollistamasta asiakkaiden paremmasta tavoittavuudesta sekä lisätuloista. Prosessi saattaa kuitenkin lisätä organisaation sisäistä monimutkaisuutta, johon yritykset pyrkivät vastaamaan operoimalla rinnakkaisia liiketoimintamalleja tai erottamalla liiketoimintamallit toisistaan. Tulokset lisäävät empiiristä näyttöä aikaisempaan kirjallisuuteen ja tukevat liikkeenjohtoa liike-toimintamalli-innovaatiotoiminnassa lisäämällä ymmärrystä datan tarjoamista mahdollisuuksista ja liiketoimintamalli-innovaatioprosesseista pk-yrityksissä.